Open-weather: Speculative-feminist propositions for planetary images in an era of climate crisis. Issue 137 (December 2022) - Engelmann, Sasha; Dyer, Sophie; Malcolm, Lizzie; Powers, Daniel
Highlights: Speculative feminist practices can transform the production of images of earth. Intersectional feminism and speculative pragmatism are allied approaches. Fractals offer a valuable alternative to whole-earth aesthetics and ontologies. open-weather proposes a methodology for imaging the earth with a citizen network. Imaginaries are accountable to the worlds from which they emerge. Abstract: This article explores how speculative feminist practices can contribute to the collection and production of images of a planet in climate crisis. Inspired by feminist geographers and the speculative pragmatism of Didier Debaise and Isabelle Stengers, we suggest how speculative and feminist thinking unsettles the mediated optics of contemporary satellite earth observation. In a speculative feminist framework, earth images may transcend their dominant roles as scientific tools and cultural allegories and become tactical devices for imagining and acting otherwise. To illustrate this, we draw empirically from the work of the feminist artistic project open-weather to make three propositions: first, envisioning a fractal earth; second, writing experience into remotely-sensed images; and third, recording the more-than-meteorological weather. Images and imaginaries of earth are not only co-constitutive of the material conditions and worlds that produce them; in a speculative feminist framework, these images and imaginaries are also accountable to these worlds.